A general method for the synthesis of heterocyclic dithiocarboxylate betaines: Potential precursors of NHC based on a novel type of functionalization of the methyl group. Issue 35 (27th August 2020) - Morkovnik, Anatolii; Zubenko, Alexander; Divaeva, Lyudmila; Demidov, Oleg; Gribanova, Tatyana; Sochnev, Vadim; Klimenko, Alexander; Dobaeva, Natalia; Borodkin, Gennadii; Drobin, Yuriy; Fetisov, Leonid; Kononenko, Kristina
Graphical abstract: Highlights: The methyl group can transform into dithiocarboxylate under the action of S8. This was shown using the quaternized C-methylheteroarenes as objects. A novel method of the synthesis of dithiocarboxylate betaines was developed. Such betaines are interesting as ligands and synthons for organic synthesis. Abstract: A more general, non-carbene route to heterocyclic dithiocarboxylate betaines was developed based on a novel type of functionalization of the C-methyl group of heterocyclic quaternary salts under the action of sulfur. These types of betaines are of interest as possible precursors for N -heterocyclic carbenes and metal complex catalysts.